2015
DOI: 10.1371/journal.pone.0124507
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Evaluation of a Loop-Mediated Isothermal Amplification Method for the Rapid Detection of Salmonella enterica serovar Typhi

Abstract: Typhoid fever remains a public health threat in many countries. A positive result in traditional culture is a gold-standard for typhoid diagnosis, but this method is time consuming and not sensitive enough for detection of samples containing a low copy number of the target organism. The availability of the loop-mediated isothermal amplification (LAMP) assay, which offers high speed and simplicity in detection of specific targets, has vastly improved the diagnosis of numerous infectious diseases. However, littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…Some studies have found LAMP is able to detect five to a few tens of copies of plasmid and genomic DNA, a detection sensitivity that is 10 times higher than conventional PCR (Fan et al 2015;Nakao et al 2010;Notomi et al 2000;Zhou et al 2014). …”
Section: Detection Sensitivitymentioning
confidence: 99%
“…Some studies have found LAMP is able to detect five to a few tens of copies of plasmid and genomic DNA, a detection sensitivity that is 10 times higher than conventional PCR (Fan et al 2015;Nakao et al 2010;Notomi et al 2000;Zhou et al 2014). …”
Section: Detection Sensitivitymentioning
confidence: 99%
“…1 was modified from Notomi et al (2000). [Colour figure can be viewed at wileyonlinelibrary.com] instance, Salmonella typhi (Abdullah et al 2014;Fan et al 2015), Campylobacter jejuni and Campylobacter coli (Pham et al 2015), and Helicobacter pylori (Bakhtiari et al 2016;Yari et al 2016). Other successful examples of LAMP usage include Neisseria meningitidis (Lee et al 2015), Listeria monocytogenes (Birmpa et al 2015;Wang et al 2015b;Ye et al 2015), Entamoeba histolytica (Rivera and Ong 2013;Singh et al 2013;Mwendwa et al 2017), and human leptospirosis (Seesom et al 2015;Hsu et al 2017).…”
Section: B3cmentioning
confidence: 99%
“…However, they still suffer from insufficiencies and inadequacies. All these methods require a sophisticated instrument for amplification and detection or elaborate methods for performance (Fang et al 2008). As a result, researchers and scientists have worked hard to overcome these limitations.…”
Section: Introductionmentioning
confidence: 99%
“…29) To simplify the DNA extraction procedure, a simple method for sample preparation was evaluated for the LAMP assay. 30,31) Supernatants of heat-treated samples following proteinase treatment were used as DNA template. As indicated in Fig.…”
Section: )mentioning
confidence: 99%